Placing Islam Geographies of Connection in Twentieth-Century Istanbul - Hammond, Timur (University of California Press, 2023)
For centuries, the Mosque of Eyüp Sultan has been one of Istanbul's most important pilgrimage destinations, in large part because of the figure buried in the tomb at its center: Halid bin Zeyd Ebû Eyûb el-Ensârî, a Companion of the Prophet Muhammad. Timur Hammond argues here, however, that making a geography of Islam involves considerably more. Following practices of storytelling and building projects from the final years of the Ottoman Empire to the early 2010s, Placing Islam shows how different individuals and groups articulated connections among people, places, traditions, and histories to make a place that is paradoxically defined by both powerful continuities and dynamic relationships to the city and wider world. This book provides a rich account of urban religion in Istanbul, offering a key opportunity to reconsider how we understand the changing cultures of Islam in Turkey and beyond. "Timur Hammond's reimagining of Eyüp is lively and erudite, bringing readers a fresh understanding of the spaces and tempos in Istanbul as a place of Islam. The result is thrilling: a story of Islam and placemaking that is at once intricately grounded and expansively illuminating." - ANNA J. SECOR, Professor of Geography, Durham University "An impressive ethnographic and textual work. Hammond provides new insight into the inner workings of a sacred site and pilgrimage center, making this a valuable contribution to the literature on urban anthropology and lived Islam." - M. BRETT WILSON, Director of the Center for Eastern Mediterranean Studies and Associate Professor of History and Public Policy at Central European University"